2014
DOI: 10.4236/msce.2014.28001
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in Cation Exchange Capacity of Zeolites at Neutral pH: Examples and Proposals of a Determination Method

Abstract: Cation exchange capacity (CEC) is an important characteristic of zeolites, especially when they are used as adsorbents in the aqueous system. However, no international standard method exists for the determination of CEC of zeolites. We determined CEC of Linde-type A and Na-P1 type zeolites at various pH (4 to 10) with a simple method, where Na +-saturated zeolites were prepared, and then various amounts of HCl were added. CEC was simply calculated by subtracting the amount of Na + in the final supernatant from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…This finding has been contrary to what has been thought all along: that the CEC of zeolites does not change with change in aqueous pH. This concept has been inferred from the fact that the CEC of 2:1 type layer silicate clay minerals such as montmorillonite is constant even at acidic conditions such as pH 4 [30,32]. Such logic possibly led to the determination of CEC without considering the effect of H + adsorption.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…This finding has been contrary to what has been thought all along: that the CEC of zeolites does not change with change in aqueous pH. This concept has been inferred from the fact that the CEC of 2:1 type layer silicate clay minerals such as montmorillonite is constant even at acidic conditions such as pH 4 [30,32]. Such logic possibly led to the determination of CEC without considering the effect of H + adsorption.…”
Section: Introductionmentioning
confidence: 90%
“…In some of the aforementioned applications, zeolites are used in a wide range of pH from acidic to alkaline conditions in aqueous media. However, our recent study showed that cation exchange capacity (CEC) Na + retention by zeolites is greatly affected by the adsorption of H + , even in the neutral pH region [30]. The adsorption of H + into zeolites results in the loss of the negative charge due to neutralization forming covalent bonds from the Lewis acid-base reaction [29,31].…”
Section: Introductionmentioning
confidence: 99%
“…In this set of measurements we made samples that contained soil as blank, zeolites only and soil with zeolites and redistilled water was added up to 500 g. Concentrations of zeolites added to samples were 0.5%, 2% and 5% calculated relativ to 500 g mixture as presented in table 1 and table 2 Table 2 shows pH values that remain constant after zeolite addition in soil, for all the three cases (concentration of zeolite in the mixture of 0.5 %, 2 % and 5 % respectively. Natural zeolites generally have the capacity to decrease soils pH [7]. However, given the bufferig capacity of soils, if small quantities of zeolite are added, soil mixture pH does not significantly change.…”
Section: 1mentioning
confidence: 99%
“…The available protons are the ones that contributed to the wider range of pH change at equilibrium. In their study on the decrease in the CEC of zeolites at neutral pH, Munthali et al [26] highlighted the pH dependence of Na + -saturated A4 and Na-P1 zeolites. With increasing the amount of HCl addition to the zeolites, equilibrium pH decreased, and CEC or the amount of Na + retained of the two zeolites decreased.…”
Section: Ph Dependence Of Pb Adsorptionmentioning
confidence: 99%